The Computing of the Influence of a Steady Element on the Polarization Spectrum - R. Cimbala; I. Kršňák; I. Kolcunová (Acta Polytechnica, 2003)
This paper describes computation of the influence of a steady current element on the current response of insulation material. The steady element is always present. When the insulation is dry, it can be neglected. When moisture is present, the steady element has to be calculated. A decision can be made after examining the spectrum.